Educational policy: Strategies for successful implementation of Independent Curriculum in transformational schools secondary education levels - Hotmaulina Sihotang; Julinda Siregar (S&Co Publishing, 2024)
The research aims to reveal and disseminate strategies success for implementing the Independent Curriculum in transformational schools. A qualitative approach with descriptive analysis method. The research focus is on school success strategies in implementing government policies for and sub-focus of the intracurricular curriculum and implementing the Pancasila student profile project. There were 14 respondents consisting of two principals, four vice principals for curriculum, four teachers, and four parents of students. An in-depth interview was used to collect the data. Data analysis by reducing the data obtained to answer the problem. The results of the research are (1) the success strategy for implementation of Independent Curriculum, namely that all stakeholders have a mindset that is willing to change to produce graduates who have competencies according to the profile of Pancasila students; (2) implementation of Independent Curriculum's successful strategy is socialized and teachers are provided with the training. The implication of this research is that these two schools exemplify service excellence for other schools so that the implementation of the Independent Curriculum can be accelerated.